Gender Abuse in Intimate Relationships: From Structural Coupling Theory to Emergence of Couple System - Condorelli, Rosalia (Scientific Research Publishing, 2017)
Is love predictable in its choices? Linear Determinism, Randomness or Complexity? By applying theoretical coordinates of current sociological interpretations of intimacy and conceptual categories of New General System Theory, the paper reflects on one-factor and linear determinism implicitly underlying mate selection processes in Structural Coupling Theory and its implications for Intimate Partner Violence (IPV). Assuming personality structure as the predictor of partner choice as well as victimization risk, SCT circumscribes victimization risk just to one category of women (insecure/avoidant women coupling with ambivalent partners). We propose that adaptive complex system and non-banal machine concepts are more effective to understand the mate selection process than linear deterministic approach, which appears too mechanistic for a process that exhibits an inextricable dimension of uncertainty and unpredictability. Research results on a sample of 100 victims of IPV do not corroborate the linear one-factor determinism underlying Structural Coupling Theory neither its implications. Rather they go in the direction of Complexity
Keywords: Adaptive Complex Systems; Complexity and Nonlinearity; Emergence of Couple System; The Volatility of Love; Love and Identity in Post-Modern Societies; Partner Choice; Gender Abuse